(untitled) (Scientific journal of the Fergana State University, 2023)
Based on the analysis of Latin-language sources, the article highlights the formation and development of the tradition of Arabic-Hebrew-Latin translation in Spanish cities such as Barcelona, Pamplona, Zaragoza and Segovia, as well as the activities of translation scientists involved in this process. The author, based on the results of his research, came to the conclusion that these four cities should be attributed to the second category in the system of medieval European translation centers, where translators acted independently.